Long noncoding RNA TFAP2A‐AS1 promotes oral squamous cell carcinoma cell growth and movement via competitively binding miR‐1297 and regulating TFAP2A expression. Issue 9 (22nd June 2022) - Yang, Kaicheng; Niu, Yunfeng; Cui, Zifeng; Jin, Linyu; Peng, Shixiong; Dong, Zhiming
Abstract: Oral squamous cell carcinoma (OSCC) is an aggressive and common malignancy in the head and neck, characterized by poor prognosis and high incidence. This study aimed to investigate the role of long noncoding RNA TFAP2A‐AS1 in OSCC. The competing endogenous RNA network of TFAP2A‐AS1 was constructed by bioinformatics analysis. The expressions of miR‐1297, TFAP2A‐AS1, and TFAP2A were measured by quantitative reverse transcription‐polymerase chain reaction. The correlations of TFAP2A‐AS1, miR‐1297, and TFAP2A with clinicopathological characteristics of OSCC were assessed. RNA immunoprecipitation and dual‐luciferase reporter assay were used to identify the target of miR‐1297. Cell proliferation was measured by colony formation assay and [3‐(4, 5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H‐tetrazolium] assay. Transwell assay and wound healing assay were performed to assess cell movement. TFAP2A‐AS1 and TFAP2A were upregulated in OSCC and their expression levels were positively correlated. The levels of TFAP2A‐AS1, miR‐1297, and TFAP2A were also associated with lymphatic metastasis and the tumor‐node‐metastasis (TNM) stage of OSCC patients. TFAP2A‐AS1 acted as a miR‐1297 sponge. OSCC cell growth and movement were inhibited by miR‐1297. Changes in the miR‐1297 expression abolished the effects of TFAP2A‐AS1 on OSCC cells. Additionally, TFAP2A was a target of miR‐1297. TFAP2A promoted OSCC cell growth and migration/invasion, indicating that TFAP2A mediated the effects of TFAP2A‐AS1 and miR‐1297. TFAP2A‐AS1 exerts an oncogenic effect in OSCC via the TFAP2A‐AS1/miR‐1297/TFAP2A axis, which may provide new targets and strategies for OSCC treatments